2022
DOI: 10.1177/08862605221082740
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Peer Victimization and Deliberate Self-Harm: A Three-Wave Moderated Mediation Model

Abstract: Background: Identifying deliberate self-harm (DSH) and peer victimization in adolescents is a public health issue. The present study evaluates a three-wave longitudinal model to examine the effect of peer victimization on DSH and the roles of internalizing problems (depression and anxiety) and perceived peer and teacher support climate in this relationship. Methods: The participants were 2381 adolescents (51.2% boys, Mage = 13.38, SD = .59) from Chinese middle schools. Self-report measures were used to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Therefore, depression is an important, underlying psychosocial mechanism that clarifies that peer victimization is associated with more NSSI. This finding is congruent with the vulnerability-stress model [ 8 ], as well as previous research showed that depression can mediate the relation between negative interpersonal relationship (such as peer victimization) and problem behaviors [ 7 , 10 , 31 ]. A previous study [ 32 ] specifically examined the influence of peer victimization and depression on NSSI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, depression is an important, underlying psychosocial mechanism that clarifies that peer victimization is associated with more NSSI. This finding is congruent with the vulnerability-stress model [ 8 ], as well as previous research showed that depression can mediate the relation between negative interpersonal relationship (such as peer victimization) and problem behaviors [ 7 , 10 , 31 ]. A previous study [ 32 ] specifically examined the influence of peer victimization and depression on NSSI.…”
Section: Discussionsupporting
confidence: 89%
“…This may be because they experience a sense of being unworthy and disconnected from peers, which can trigger fierce dysfunctional emotional responses and states, such as depression [ 9 ]. According to a three-wave longitudinal study of 2381 Chinese adolescents, Wei et al [ 10 ] demonstrated that peer victimization could positively predict depression in the next 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, depression is an important, underlying psychosocial mechanism that clari es that peer victimization is associated with more NSSI. This nding is congruent with the vulnerability-stress model [8], as well as previous research that showed that depression can mediate the relation between peer victimization and problem behaviors [7,10]. Previous studies [27] speci cally examined the in uence of peer victimization and depression on NSSI.…”
Section: Discussionsupporting
confidence: 86%
“…This is because they experience a sense of being unworthy and disconnected from peers, which can trigger erce dysfunctional emotional responses and states, such as depression [9]. With a three-wave longitudinal study of 2381 Chinese adolescents, Wei et al [10] demonstrated that peer victimization could positively predict depression in the next six months.…”
mentioning
confidence: 99%
“…Previous empirical evidence has found that strains could lead to negative emotions and affect subsequent addictive behaviors (Peck et al, 2018; Unnever & Cornell, 2003). Individuals experiencing peer victimization experience negative emotions (Stapinski et al, 2015; Wei et al, 2022). For example, a meta-analytic review showed that peer victimization is more strongly associated with depression than other types of psychological distress (Hawker et al, 2000).…”
Section: Introductionmentioning
confidence: 99%